Alkaline earth metals loading on waste deoiled-spent bleaching clay as catalysts in transesterification reaction - Maniam, Gaanty Pragas; Ab. Rahim, Mohd Hasbi; Jose, Rajan (2017)
In the present work, waste sources, namely spent bleaching clay, has been successfully utilized as solid catalysts support in the transesterification of refined, bleached and deodorized palm olein (RBD-PO), waste palm cooking oil (WPCO) and spent bleaching clay oil (SBC) to produce methyl esters (biodiesel). Energy plays an important role in social, economy, development of the country as well as our daily life. Biodiesel is one of the alternative ways to replace fossil fuels as the energy source. It is renewable and environmental friendly. Biodiesel are usually made from the reaction between triglycerides and alcohol under presence of catalyst through transesterification reaction. The triglycerides source from waste source such as WPCO and SBC can help to reduce the production cost and do not cause food issue. In order to enhance the catalytic activity, the deoiled SBC had been calcined at 500 °C for 10 h and doped with KOH, CaO and La2O3. The catalyst was characterized with TGA, FTIR, XRD, XRF, BET, FESEM and Hammett indicators (phenolphthalein, 2,4-dinitroaniline and 4- nitroaniline). The optimal reaction conditions found to be: for transesterification of RBD-PO using K-DSBC was 3 wt.% catalyst amount while for Ca-DSBC and La- DSBC were 5% catalyst (based on oil weight) and 9:1 methanol to oil molar ratio for 2 h reaction period producing 99.0%, 98.8% and 96.2% methyl ester conversion respectively. Meanwhile in transesterify WPCO, K-DSBC was 3 wt.% catalyst amount while for Ca-DSBC and La-DSBC were 5% catalyst (based on oil weight) and 9:1 methanol to oil molar ratio for 3 h reaction period producing 97.2%, 85.5% and 83.1% methyl ester conversion respectively. Transesterification of SBC oil using K-DSBC was 3 wt.% catalyst amount while for Ca-DSBC and La-DSBC were 5% catalyst (based on oil weight) and 9:1 methanol to oil molar ratio for 4 h reaction period producing 88.9%, 80.2% and 76.6% methyl ester conversion respectively.. All catalysts undergo transesterification at the reflux temperature of methanol (65 °C). Furthermore, the regenerated of the catalytic activity was investigated, and found that all the three catalysts could be reused up to five times, when maintaining methyl esters content above 90%. In addition, the catalysts exhibit tolerance towards the presence of water at 1.75% and 2.0% and free fatty acid at 1.75% and 1.75%, respectively, with over 80% of methyl esters content.